2017
DOI: 10.1007/s00709-017-1138-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium ion transporters and osmotic adjustments in stress alleviation of Cynodon dactylon under NaCl treatment: a parallel investigation with rice

Abstract: Comparative analyses of the responses to NaCl in Cynodon dactylon and a sensitive crop species like rice could effectively unravel the salt tolerance mechanism in the former. C. dactylon, a wild perennial chloridoid grass having a wide range of ecological distribution is generally adaptable to varying degrees of salinity stress. The role of salt exclusion mechanism present exclusively in the wild grass was one of the major factors contributing to its tolerance. Salt exclusion was found to be induced at 4 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This result suggested that the salt tolerance strategy of seashore paspalum was via maintaining high K + concentration in the shoots and repressing Na + transference from roots to shoots when exposed to salt stress. In bermudagrass, in addition to higher K + concentration in shoots, Na + exclusion from the surface of leaves was also observed under salt stress [30]. The results implied that unlike seashore paspalum, bermudagrass preferred the strategy of Na + exclusion to withstand salt stress.…”
Section: Salt Stressmentioning
confidence: 86%
“…This result suggested that the salt tolerance strategy of seashore paspalum was via maintaining high K + concentration in the shoots and repressing Na + transference from roots to shoots when exposed to salt stress. In bermudagrass, in addition to higher K + concentration in shoots, Na + exclusion from the surface of leaves was also observed under salt stress [30]. The results implied that unlike seashore paspalum, bermudagrass preferred the strategy of Na + exclusion to withstand salt stress.…”
Section: Salt Stressmentioning
confidence: 86%
“…Variations in its amino acid sequences result in a change in Na + affinity and a subsequent change in salt tolerance in two species of Triticum. Comparative analysis of antioxidant mechanisms in Cynodon dactylon (salt-tolerant grass) and Oryza sativa (salt-sensitive plant) was corroborated by the high expression levels of SOS 1 and NHX1 transporters in Cynodon [159]. Salt tolerance in barley has been attributed to the regulation of Na + loading in root xylem elements [160].…”
Section: Ion Transporters Mediating Role In Salt Tolerancementioning
confidence: 94%
“…On the other hand, salt-sensitive varieties are unable to sequester salt in vacuoles and the salt accumulates rapidly in the cytoplasm followed by a reduction of photosynthesis and assimilation [ 2 , 11 ]. Salt stress causes various physiological changes such as: (1) decrease in the rate of photosynthesis [ 2 , 12 , 13 , 14 , 15 ]; (2) smaller stomatal aperture and lower stomatal conductance due to disturbed water relations and sensitivity to abscisic acid (ABA) [ 2 , 12 , 13 , 15 , 16 , 17 ]; (3) decrease in transpiration rate [ 12 , 18 , 19 ]; (4) decrease in chlorophyll a and b, total chlorophyll, and carotenoids concentrations [ 14 , 17 , 20 , 21 , 22 , 23 ]; (5) decrease in chlorophyll fluorescence [ 15 , 24 , 25 , 26 ]; (6) changes in leaf anatomy, such as a decrease in the thickness of the epidermis and mesophyll and a decrease in intercellular spaces in the leaves [ 27 , 28 ], and a reduction in root length density [ 29 , 30 ]; (7) nutrient imbalance with a decrease in the content of phosphorus, nitrogen, Ca 2+ , Mg 2+ , and K + [ 21 , 31 ]; (8) decrease in leaf relative water content [ 8 , 32 , 33 , 34 , 35 ]; (9) membrane instability and increase in membrane permeability [ 35 , 36 , 37 , 38 ].…”
Section: Physiological Effects Of Salt Stressmentioning
confidence: 99%